Conflictos regionales : tendencias en un período de transición - Cintra, José Thiago (Estudios Internacionales, 1989)
Relations between the superpowers are in a period of transition. The intention of this document is to outline those currents of regional conflict that may develop from the current détente, assuming the premise of a decline in the military involvement of the superpowers. In this context, there are at least three possible trends in regional conflicts. The first refers to conflicts whose origins can be found in the ideological and strategic inertia that developing countries have inherited from the East-West rivalry. The second is related to the current détente and is characterized by a "decompression effect", influenced by the superpowers. The third case, more difficult to analyze, has less roots in East-West relations than in North-South conflict and has important implications for the evolution of the domestic order.